2013
DOI: 10.2214/ajr.12.10511
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous CT-Guided Radiofrequency Ablation as Supplemental Therapy After Systemic Chemotherapy for Selected Advanced Non–Small Cell Lung Cancers

Abstract: Percutaneous CT-guided RFA can be performed as a feasible minimally invasive supplemental therapy with satisfactory PFS after systemic chemotherapy for patients with advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
0
27
1
Order By: Relevance
“…As regard the immediate complications of thermoablation in the current study were less than that reported by Herrera et al, [22] who reported pleural effusion in 9 of 18 patients (50%), pneumothorax in 7 patients (53.8%), delayed pneumothorax in one patient 5%, pneumonia in 4 patients 22%, transient acute respiratory failure in one patient 5% and massive hemoptysis in one patient 5%, Li et al, [23] who reported that there were no death related to the RFA procedure. The major complication was pneumothorax requiring chest tube placement, which occurred in (11.9%).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…As regard the immediate complications of thermoablation in the current study were less than that reported by Herrera et al, [22] who reported pleural effusion in 9 of 18 patients (50%), pneumothorax in 7 patients (53.8%), delayed pneumothorax in one patient 5%, pneumonia in 4 patients 22%, transient acute respiratory failure in one patient 5% and massive hemoptysis in one patient 5%, Li et al, [23] who reported that there were no death related to the RFA procedure. The major complication was pneumothorax requiring chest tube placement, which occurred in (11.9%).…”
Section: Discussioncontrasting
confidence: 43%
“…These findings were comparable to Lee et al, [19] who reported an overall complete necrosis rate of 38% at a mean follow-up of 12.5 months, they reported that tumor size measuring 3 to 5 cm were completely ablated in 38% of cases and lesions greater than 5 cm had only a 8% complete necrosis rate. In a study done by Li et al, [23] 31 patients (63.3%) had a complete response, 12 patients (24.5%) had a partial response, six patients (12.2%) had stable disease, and no patients had progressive disease. In a study done by Chua et al, [24] of 148 patients treated, 66 patients (46%) had a complete response, 38 patients (26%) had a partial response, 57 patients (39%) had stable disease and 23 patients (16%) had progressive disease.…”
Section: Discussionmentioning
confidence: 94%
“…The summary of 27 studies is listed in Table 2 [5-15, 17-22, 30, 31, 33-40]. The mean age of included studies was beyond 45.7 years, and 62.2% were males.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the lung tumors were completely or partially ablated. The complication rate occurred in percutaneous CT-guided RFA was 12.8%-24.6% [8, 9] and in MWA was 11.9%-66.7% [5, 7]. Li et al used CT-guided RFA percutaneously as a supplemental therapy for selected advanced non-small cell lung cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation